Digital Financial Literacy and Financial Technology on Financial Performance through Financial Behavior as a Mediating Variable - Wulandari, Nur Apni; Purwidianti, Wida; Nurul Innayah, Maulida; Frida Utami, Restu (Airlangga Journal of Innovation Management, 2025)
This research analyzes the effect of digital financial literacy and financial technology on financial performance, with financial behavior as a mediator. The population used is the MSE actors in the South Brebes Regency area, consisting of 6 sub-districts. Sampling using the convenience sampling technique calculated by the Slovin formula, resulting in 110 participants. The data were collected through the distribution of questionnaires using a Likert scale, and then examined with SmartPLS 3.0 software. According to the results, adopting fintech is not the only way for MSEs to achieve excellent financial performance; responsible financial behavior and a firm understanding of digital financial literacy are also essential. Theoretically, this study highlights that enhancing MSE financial performance requires a combination of financial expertise and efficient technology use, since technology is insufficient on its own without the capacity to understand and utilize financial data strategically. From a managerial standpoint, the findings suggest that improving MSE actors’ financial capabilities, especially their comprehension, interpretation, and application of digital financial tools and concepts, is essential to guaranteeing that fintech solutions can be utilized efficiently. In an increasingly digital economic world, this capacity helps business owners make strategic, sustainable, and well-informed decisions that support the long-term resilience and success of their companies.